The Role of Peer Rejection in Adolescent Internalizing Problems - Nandy Agustin Syakarofath; Ananda Nabilah Biorohmi; Latipun Latipun (Faculty of Psychology, Diponegoro University, 2021)
Emotional distress, such as symptoms of anxiety, depression, and withdrawal, is on the rise among teenagers today. These symptoms are generally grouped into internalizing problems. Based on research, a risk factor that contributes to internalizing problems is peer rejection. This study aims to determine the effect of peer rejection on adolescent internalizing problems. Research design is quantitative research with a multistage random sampling technique as a data collection technique. The subjects of this study were 252 adolescents aged 16-18 years who are currently studying in SMA in Bondowoso Regency, consisting of 103 boys (M = 40.068; SD = 13.283) and 149 girls (M = 40.893; SD =13.283). The instruments used were Social Peer Rejection Measure (21 items, α = .90) and Strengths and Difficulty Questionnaire (SDQ), just for internalizing problems (10 items, α = .72). The results of the analysis test using simple linear regression showed that there was a positive influence of peer rejection on internalizing problems in high school adolescents in Bondowoso Regency, adjusted R 2 = .278; F(4, 427) = 251, p = .000). This influence shows that the more often adolescents experience rejection from their peers, the higher the chances of experiencing internalizing problems.